Actual problems of formation of the XXI century (Herald of Journalism, 2020)
At leading universities of the country innovative technologies for de velopment of scientific projects are introduced. It is important for entry  of our university into uniform cultural and educational world space and meets the modern requirements of modernization of domestic education and its competitiveness in the conditions of entry into it into number of 50 front lines and the hitech countries of the world.
Keywords: education, innovation, training methods.